Key Factors in Big Data Implementation for Smart City: A Systematic Literature Review - Safitri, Yulida (FIA UB, 2021)
Many governments implement smart city concept in their daily operation. As the concept continues to develop, smart cities all over the world are now starting to utilize big data. Learning from their private counterparts that already ahead in harnessing the potential benefits of big data implementation, smart cities begin the transformation of implementing big data. The purpose of this research paper is to: 1) Review the possible opportunities offered by big data implementation in smart city, 2) Review the challenges that smart city need to solve in utilizing big data, 3) Develop a framework that addresses the key factors in successful big data implementation in smart city. This research paper produces a framework that addresses several key factors that smart city government should consider ensuring success when implementing big data based on the proposed model indicators in private sectors. This framework consists of key factors of big data implementation for smart city which are top management support, organizational change, privacy and security, data availability and quality, cost, skillset and knowledge, big data policy, and technological infrastructure. It is important to have an understanding that these key factors correlate each other and are equally important.